Evaluation of the relationship between the muscle involvement and the appearance of rectal endometriosis in MRI imaging - Mirzakhani, Mahdieh; Nasiri, Saeid; Haghgoo, Ameneh Sadat (Researcher Bulletin of Medical Sciences, 2026)
Objective: MRI is a non-invasive imaging technique with high accuracy for detecting the appearance features of endometriosis, including rectal endometriosis. The degree of muscle involvement is also an important factor in determining the degree and progression of rectal endometriosis, which is based on the results of histopathology. The aim of this study is to investigate the relationship between the degree of muscle involvement and the appearance features of rectal endometriosis in patients referred to the Imam Hossein Medical and Educational Center in 2021 to 2023; so that by determining the relationship between the appearance features of endometriosis and the degree of involvement of the rectal muscle, we can predict the degree of muscle involvement and the progression of endometriosis using MRI as a non-invasive method compared to histopathology Materials and Methods: The present study is a descriptive-analytical study conducted on 144 patients with rectal endometriosis who referred to Imam Hossein Hospital between 2021 and 2023. In this study, patients who underwent MRI before surgery or histopathology of rectal endometriosis were included. The data were analyzed using SPSS version 27 software and logistic regression test. Results: The results of two-level logistic regression analysis show that there is a significant relationship between the variable of muscle involvement and the length and number of rectal endometriosis (P-value <0.05). So that for each unit increase in length, the chance of muscle involvement increases by a factor of 1.03 and for each unit increase in the number of involved nodules, the chance of muscle involvement increases by a factor of 4.65. The results also show that there is no significant relationship between the variable of muscle involvement and the thickness of rectal endometriosis (P-value >0.05). Conclusion: According to the results obtained from the two-level logistic regression test, it can be understood that the length and number of rectal endometriosis nodules have a positive effect on muscle involvement and increase the chance of muscle involvement. While the thickness of rectal endometriosis has almost no effect on muscle involvement.